Variations in pass-through from global agricultural commodity prices to domestic food inflation - Daniel Hyun; Jacky Lee (Bank of Canada, 2023)
This paper examines factors that affect the transmission of fluctuations in global agricultural commodity prices to domestic food inflation. Using panel regressions on data from 53 advanced and emerging-market countries, we investigate how factors such as local crop production conditions, the extent of food industry development and the net agricultural trade status interact with global agricultural prices to affect pass-through to local food prices. Results show that pass-through varies significantly based on these factors. Pass-through decreases during better-than-normal crop conditions, highlighting the importance of local production. Countries with less-developed food industries experience higher pass-through, likely due to the greater importance of raw commodities in diets and less-complex supply chains. Interestingly, net exporters of agricultural commodities exhibit greater pass-through, potentially due to strategic trade adjustments that take advantage of global supply and demand dynamics. These variations in pass-through suggest potential avenues for managing food price inflation in response to shocks to global food prices under different scenarios.
Keywords: E31; Q02; Q11; Q17; Q18; 330; Inflation and prices; International topics